The continuing conundrum in oligometastatic breast carcinoma: A real-world data. (June 2022) - Selvarajan, Gangothri; Dhanushkodi, Manikandan; Radhakrishnan, Venkatraman; Kalaiyarasi, Jayachandran Perumal; Murali, Carthikeyan Subramaniam; Ananthi, Balasubramanian; Iyer, Priya; Krishnamurthy, Arvind; Velusamy, Sridevi; Ganesarajah, Selvaluxmy; Sagar, Tenali Gnana
Abstract: The optimal management in Oligometastatic (OM) breast carcinoma is not defined. Objectives: To identify the prognostic factors influencing OM and the effect of Locoregional treatment (LRT) on survival in OM. Methodology: Patients with ≤5 metastases and each with ≤ 5 cm size were defined as OM. Data of OM were extracted from the Institute Registry between 2012 and 2018. The impact of prognostic factors on survival was analysed by univariate and multivariate Cox regression. The Kaplan Meier survival curves were used to plot PFS and OS. Results: There were 170 patients with OM. The median follow-up was 61 months. Median OS was 43.3 months. The median OS was 74 months in OMD vs 22.7 months in Oligorecurrent disease (ORD) with 5year OS rate of 55.3% vs 16.5% respectively. In the multivariate analyses of OMD both Ki67 ≤ 50% and hormone therapy (HT) showed significant favourable survival outcome. While premenopausal status and HT showed significant survival benefits in ORD. The worse survival outcome in ORD could be because of their aggressive biology and deficit in LRT compared to literature review. The prognostic factors were swayed by the uneven distribution of HR status, grade and Ki67. Conclusion: The survival of OM was influenced by OMD, Ki67 ≤ 50%, premenopausal status and HT. The lesser survival rates of OM in the long term suggest the need for curative LRT to metastatic sites and primary tumor. The potential role of HT and targeted therapy with or without LRT need to be assessed in future randomised trials. Highlights: Analysis of Oligometastases (OM) defined as ≤ 5 metastases and each ≤ 5 cm amenable to local therapy. Favourable survival outcomes observed for the denovo OM at diagnosis (OMD), Ki67 ≤ 50%, premenopausal status and hormone therapy (HT). Aggressive biology and deficit of curative locoregional treatment (LRT) hint the lesser survival rates observed in oligorecurrent disease (ORD). The exact role of LRT to both primary and metastases need to be assessed in future prospective trials in the era of targeted therapies.